A polyurethane resin composition for display screen packaging and preparation method thereof

By adding specific raw materials to the polyurethane resin composition packaged in the display screen, the interfaceability and overall performance are optimized, and the problem of difficulty in coordinating and improving the bonding strength, water vapor barrier properties and cold and heat impact resistance in the prior art is solved, and more efficient packaging performance is achieved.

CN117603558BActive Publication Date: 2025-03-07GUANGZHOU ZANCHEN NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202311403925.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-03-07
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The adhesive strength and water vapor barrier properties of the existing polyurethane resin compositions are difficult to coordinately improve in display packaging, and their cold and cold impact resistance are insufficient, which limits the efficiency of the product.

Method used

Polyester resin and polyurethane resin are used as base materials, and silane coupling agent KH560, sheet bentonite modified whiskers, glass fiber regulators and nano-lanthanum oxide agents are added. Through the coordination and coordination of these raw materials, the interfacial properties and overall performance of the system are optimized.

Benefits of technology

It significantly improves the product's bonding strength, water vapor barrier properties and cold and heat impact resistance, achieves coordinated performance improvements, and improves the product's use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a polyurethane resin composition for display screen encapsulation, comprising the following raw materials in parts by weight: 20-25 parts of polyester resin, 10-15 parts of polyurethane resin, 45-50 parts of butanone, 6-10 parts of silane coupling agent KH560, 8-12 parts of flaky bentonite modified whisker agent, 5-10 parts of glass fiber regulator and 2-5 parts of nano lanthanum oxide agent. The polyurethane resin composition for display screen encapsulation of the invention uses polyester resin and polyurethane resin as base materials, and optimizes the interface of system raw materials by adding silane coupling agent KH560 as an interface regulator, and coordinates and synergizes the flaky bentonite modified whisker agent, glass fiber regulator and nano lanthanum oxide agent with each other, so that the bonding strength, water vapor barrier and cold and heat shock resistance of the product are coordinated and improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane resin compositions, and in particular to a polyurethane resin composition for display screen packaging and a preparation method thereof. Background Art

[0002] Early LED displays were mainly used for text display. With the advancement of manufacturing technology, electronic technology, and information technology, the display capability and application level of LED display systems have made great progress. As a new type of flat panel display device, full-color LED displays are sought after by the industry for their wide color gamut, high brightness, and large-area display capabilities.

[0003] In the prior art, a resin composition is used to complete the display screen encapsulation process. The bonding strength performance of the existing polyurethane resin composition encapsulation products is average. In order to improve the bonding strength of the product, the water vapor barrier property is reduced, and it is difficult to achieve coordinated improvement of the bonding strength and water vapor barrier property. In addition, the product's resistance to cold and heat shock is reduced, and it is difficult to achieve coordinated improvement of the product's performance, which limits the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a polyurethane resin composition for display screen encapsulation and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a polyurethane resin composition for display screen encapsulation, comprising the following raw materials in parts by weight:

[0007] 20-25 parts of polyester resin, 10-15 parts of polyurethane resin, 45-50 parts of butanone, 6-10 parts of silane coupling agent KH560, 8-12 parts of lamellar bentonite modified whisker agent, 5-10 parts of glass fiber regulator and 2-5 parts of nano lanthanum oxide agent.

[0008] Preferably, the polyurethane resin composition for display screen encapsulation is the following raw materials in parts by weight:

[0009] 22.5 parts of polyester resin, 12.5 parts of polyurethane resin, 47.5 parts of butanone, 8 parts of silane coupling agent KH560, 10 parts of lamellar bentonite modified whisker agent, 7.5 parts of glass fiber regulator and 3.5 parts of nano lanthanum oxide agent.

[0010] Preferably, the preparation method of the flaky bentonite modified whisker agent is:

[0011] S01: Send bentonite to 300-320℃ for heat treatment for 5-10min, then cool to 145-155℃ at a rate of 2-5℃ / min, and then cool to 55℃ at a rate of 1-3℃ / min;

[0012] S02: The product of S01 is transferred to a yttrium nitrate solution for immersion treatment, the immersion pressure is 5-10MPa, the immersion time is 10-20min, and after the immersion is completed, it is filtered and dried to obtain an immersed flaky bentonite agent;

[0013] S03: adding 4-7 parts of silicon carbide whiskers, 1-3 parts of sodium lignin sulfonate, and 0.35-0.45 parts of a phosphate buffer solution with a pH value of 5.5 to 10-15 parts of a 5% chitosan solution, and stirring to obtain a silicon carbide whisker solution;

[0014] S04: The immersed flaky bentonite agent and silicon carbide whisker liquid are mixed and ball-milled in a weight ratio of 5:2, with a ball-milling speed of 1000-1500 r / min and a ball-milling time of 20-30 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky bentonite modified whisker agent.

[0015] Preferably, the mass fraction of the yttrium nitrate solution is 4-8%.

[0016] Preferably, the preparation method of the glass fiber conditioning agent is:

[0017] S11: mixing glass fiber and sodium citrate solution in a weight ratio of 1:3 and feeding the mixture into a mixer;

[0018] S12: then add 2-5% of diethanolamine, 1-3% of sodium dodecylbenzene sulfonate and 1-5% of glycolic acid to the total amount of glass fiber, stir at a speed of 300-400 r / min for 10-20 min, and then finish stirring;

[0019] S13: Finally, add 4-7% of the total amount of glass fiber nano-silica sol, stir at a speed of 700-900r / min for 30-40min, wash with water and dry to obtain a glass fiber regulator.

[0020] Preferably, the mass fraction of the sodium citrate solution is 10-15%.

[0021] Preferably, the preparation method of the nano lanthanum oxide agent is:

[0022] The nano-lanthanum oxide is first irradiated in a proton irradiation box for 10-20 minutes. After the irradiation is completed, the temperature is raised to 210-220°C at a rate of 1-3°C / min, heat-treated for 10-20 minutes, then placed in a 5-10°C sodium silicate solution with stirring and cooled to room temperature, and finally washed with water and dried to obtain the nano-lanthanum oxide agent.

[0023] Preferably, the mass fraction of the sodium silicate solution is 14-18%.

[0024] Preferably, the irradiation power is 350-450W.

[0025] The present invention also provides a method for preparing a polyurethane resin composition for display screen encapsulation, comprising the following steps:

[0026] The lamellar bentonite modified whisker agent, glass fiber regulator, nano lanthanum oxide agent and silane coupling agent KH560 are sequentially added to butanone and stirred to mix well, and then polyester resin and polyurethane resin are added, stirred thoroughly at 60-65° C., and finally cooled and filtered to obtain a polyurethane resin composition for display screen encapsulation.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The polyurethane resin composition for display screen encapsulation of the present invention uses polyester resin and polyurethane resin as base materials, adds silane coupling agent KH560 as an interface regulator, optimizes the interface property of system raw materials, coordinates and synergizes with each other through the coordination of lamella bentonite modified whisker agent, glass fiber regulator and nano lanthanum oxide agent, and improves the bonding strength, water vapor barrier property and cold and hot shock resistance of the product in a coordinated manner. The lamella bentonite modified whisker agent uses lamella bentonite as the base material, and the lamella structure is interlaced in the system to play a basic role in the stability of the system, and after S01 thermal modification, the lamella structure is further improved. The interlaminar spacing is optimized, improved by immersion, and coordinated with silicon carbide whisker liquid to improve the overall performance of the system. The added glass fiber regulator is treated with diethanolamine, sodium dodecylbenzene sulfonate, glycolic acid, and nano-silica sol through multi-stage stirring and mixing, so that the synergistic effect of the glass fiber and the lamellae bentonite modified whisker agent is further enhanced. At the same time, through the addition of nano-lanthanum oxide, further coordination is achieved, so that the bonding strength, water vapor barrier, and resistance to cold and hot shock performance of the system are further improved. DETAILED DESCRIPTION

[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] A polyurethane resin composition for display screen encapsulation in this embodiment includes the following raw materials in parts by weight:

[0031] 20-25 parts of polyester resin, 10-15 parts of polyurethane resin, 45-50 parts of butanone, 6-10 parts of silane coupling agent KH560, 8-12 parts of lamellar bentonite modified whisker agent, 5-10 parts of glass fiber regulator and 2-5 parts of nano lanthanum oxide agent.

[0032] The polyurethane resin composition for display screen encapsulation of this embodiment is composed of the following raw materials in parts by weight:

[0033] 22.5 parts of polyester resin, 12.5 parts of polyurethane resin, 47.5 parts of butanone, 8 parts of silane coupling agent KH560, 10 parts of lamellar bentonite modified whisker agent, 7.5 parts of glass fiber regulator and 3.5 parts of nano lanthanum oxide agent.

[0034] The preparation method of the flaky bentonite modified whisker agent of this embodiment is:

[0035] S01: Send bentonite to 300-320℃ for heat treatment for 5-10min, then cool to 145-155℃ at a rate of 2-5℃ / min, and then cool to 55℃ at a rate of 1-3℃ / min;

[0036] S02: The product of S01 is transferred to a yttrium nitrate solution for immersion treatment, the immersion pressure is 5-10MPa, the immersion time is 10-20min, and after the immersion is completed, it is filtered and dried to obtain an immersed flaky bentonite agent;

[0037] S03: adding 4-7 parts of silicon carbide whiskers, 1-3 parts of sodium lignin sulfonate, and 0.35-0.45 parts of a phosphate buffer solution with a pH value of 5.5 to 10-15 parts of a 5% chitosan solution, and stirring to obtain a silicon carbide whisker solution;

[0038] S04: The immersed flaky bentonite agent and silicon carbide whisker liquid are mixed in a weight ratio of 5:2 and ball-milled at a ball-milling speed of 1000-1500 r / min for 20-30 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a flaky bentonite modified whisker agent.

[0039] The mass fraction of the yttrium nitrate solution in this embodiment is 4-8%.

[0040] The preparation method of the glass fiber conditioning agent of this embodiment is:

[0041] S11: mixing glass fiber and sodium citrate solution in a weight ratio of 1:3 and feeding the mixture into a mixer;

[0042] S12: then add 2-5% of diethanolamine, 1-3% of sodium dodecylbenzene sulfonate and 1-5% of glycolic acid to the total amount of glass fiber, stir at a speed of 300-400 r / min for 10-20 min, and then finish stirring;

[0043] S13: Finally, add 4-7% of the total amount of glass fiber nano-silica sol, stir at a speed of 700-900 r / min for 30-40 minutes, wash with water and dry to obtain a glass fiber regulator.

[0044] The mass fraction of the sodium citrate solution of the present embodiment is 10-15%.

[0045] The preparation method of the nano lanthanum oxide agent of this embodiment is:

[0046] The nano-lanthanum oxide is first irradiated in a proton irradiation box for 10-20 minutes. After the irradiation is completed, the temperature is raised to 210-220°C at a rate of 1-3°C / min, heat-treated for 10-20 minutes, then placed in a 5-10°C sodium silicate solution with stirring and cooled to room temperature, and finally washed with water and dried to obtain the nano-lanthanum oxide agent.

[0047] The mass fraction of the sodium silicate solution in this embodiment is 14-18%.

[0048] The irradiation power of this embodiment is 350-450W.

[0049] A method for preparing a polyurethane resin composition for display screen encapsulation in this embodiment comprises the following steps:

[0050] The lamellar bentonite modified whisker agent, glass fiber regulator, nano lanthanum oxide agent and silane coupling agent KH560 are sequentially added to butanone and stirred to mix well, and then polyester resin and polyurethane resin are added, stirred thoroughly at 60-65° C., and finally cooled and filtered to obtain a polyurethane resin composition for display screen encapsulation.

[0051] Example 1.

[0052] A polyurethane resin composition for display screen encapsulation in this embodiment includes the following raw materials in parts by weight:

[0053] 20 parts of polyester resin, 10 parts of polyurethane resin, 45 parts of butanone, 6 parts of silane coupling agent KH560, 8 parts of lamellar bentonite modified whisker agent, 5 parts of glass fiber regulator and 2 parts of nano lanthanum oxide agent.

[0054] The preparation method of the flaky bentonite modified whisker agent of this embodiment is:

[0055] S01: The bentonite was heat treated at 300°C for 5 min, then cooled to 145°C at a rate of 2°C / min, and then cooled to 55°C at a rate of 1°C / min;

[0056] S02: The product of S01 is transferred to a yttrium nitrate solution for immersion treatment, the immersion pressure is 5 MPa, the immersion time is 10 min, and after the immersion is completed, it is filtered and dried to obtain an immersed flaky bentonite agent;

[0057] S03: adding 4 parts of silicon carbide whiskers, 1 part of sodium lignin sulfonate, and 0.35 parts of a phosphate buffer solution with a pH value of 5.5 to 10 parts of a 5% chitosan solution by mass, and stirring to obtain a silicon carbide whisker solution;

[0058] S04: The immersed lamellar bentonite agent and silicon carbide whisker liquid are mixed in a weight ratio of 5:2 and ball-milled at a ball-milling speed of 1000 r / min for 20 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lamellar bentonite modified whisker agent.

[0059] The mass fraction of the yttrium nitrate solution in this embodiment is 4%.

[0060] The preparation method of the glass fiber conditioning agent of this embodiment is:

[0061] S11: mixing glass fiber and sodium citrate solution in a weight ratio of 1:3 and feeding the mixture into a mixer;

[0062] S12: then add 2% of diethanolamine, 1% of sodium dodecylbenzene sulfonate and 1% of glycolic acid to the total amount of glass fiber, stir at a speed of 300 r / min for 10-20 min, and end the stirring;

[0063] S13: Finally, add 4% of the total amount of glass fiber nano-silica sol, stir at a speed of 700 r / min for 30 minutes, wash with water, and dry to obtain a glass fiber regulator.

[0064] The mass fraction of the sodium citrate solution in this embodiment is 10%.

[0065] The preparation method of the nano lanthanum oxide agent of this embodiment is:

[0066] The nano-lanthanum oxide is first irradiated in a proton irradiation box for 10 minutes. After the irradiation is completed, the temperature is raised to 210°C at a rate of 1°C / min, heat-treated for 10 minutes, then placed in a 5°C sodium silicate solution with stirring and cooled to room temperature, finally washed with water and dried to obtain the nano-lanthanum oxide agent.

[0067] The mass fraction of the sodium silicate solution in this embodiment is 14%.

[0068] The irradiation power of this embodiment is 350W.

[0069] A method for preparing a polyurethane resin composition for display screen encapsulation in this embodiment comprises the following steps:

[0070] The lamellar bentonite modified whisker agent, glass fiber regulator, nano lanthanum oxide agent and silane coupling agent KH560 are sequentially added to butanone and stirred to mix well, and then polyester resin and polyurethane resin are added, stirred thoroughly at 60° C., and finally cooled and filtered to obtain a polyurethane resin composition for display screen encapsulation.

[0071] Example 2.

[0072] A polyurethane resin composition for display screen encapsulation in this embodiment includes the following raw materials in parts by weight:

[0073] 25 parts of polyester resin, 15 parts of polyurethane resin, 50 parts of butanone, 10 parts of silane coupling agent KH560, 12 parts of lamellar bentonite modified whisker agent, 10 parts of glass fiber regulator and 5 parts of nano lanthanum oxide agent.

[0074] The preparation method of the flaky bentonite modified whisker agent of this embodiment is:

[0075] S01: The bentonite was heat treated at 320°C for 10 min, then cooled to 155°C at a rate of 5°C / min, and then cooled to 55°C at a rate of 3°C / min;

[0076] S02: The product of S01 is transferred to a yttrium nitrate solution for immersion treatment, the immersion pressure is 10 MPa, the immersion time is 20 min, and after the immersion is completed, it is filtered and dried to obtain an immersed flaky bentonite agent;

[0077] S03: adding 7 parts of silicon carbide whiskers, 3 parts of sodium lignin sulfonate, and 0.45 parts of a phosphate buffer solution with a pH value of 5.5 to 15 parts of a 5% chitosan solution, and stirring to obtain a silicon carbide whisker solution;

[0078] S04: The immersed lamellar bentonite agent and silicon carbide whisker liquid are mixed in a weight ratio of 5:2 and ball-milled at a ball-milling speed of 1500 r / min for 30 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lamellar bentonite modified whisker agent.

[0079] The mass fraction of the yttrium nitrate solution in this embodiment is 8%.

[0080] The preparation method of the glass fiber conditioning agent of this embodiment is:

[0081] S11: mixing glass fiber and sodium citrate solution in a weight ratio of 1:3 and feeding the mixture into a mixer;

[0082] S12: then add 5% of diethanolamine, 3% of sodium dodecylbenzene sulfonate and 5% of glycolic acid to the total amount of glass fiber, stir at a speed of 400 r / min for 20 min, and then end the stirring;

[0083] S13: Finally, add 7% of the total amount of glass fiber nano-silica sol, stir at a speed of 900 r / min for 40 minutes, wash with water, and dry to obtain a glass fiber regulator.

[0084] The mass fraction of the sodium citrate solution in this embodiment is 15%.

[0085] The preparation method of the nano lanthanum oxide agent of this embodiment is:

[0086] The nano-lanthanum oxide is first irradiated in a proton irradiation box for 20 minutes. After the irradiation is completed, the temperature is raised to 220°C at a rate of 3°C / min, and heat-treated for 20 minutes. Then, it is placed in a 10°C sodium silicate solution and stirred to cool to room temperature. Finally, it is washed with water and dried to obtain the nano-lanthanum oxide agent.

[0087] The mass fraction of the sodium silicate solution in this embodiment is 18%.

[0088] The irradiation power of this embodiment is 450W.

[0089] A method for preparing a polyurethane resin composition for display screen encapsulation in this embodiment comprises the following steps:

[0090] The lamellar bentonite modified whisker agent, glass fiber regulator, nano lanthanum oxide agent and silane coupling agent KH560 are sequentially added to butanone and stirred to mix well, and then polyester resin and polyurethane resin are added, stirred thoroughly at 65° C., and finally cooled and filtered to obtain a polyurethane resin composition for display screen encapsulation.

[0091] Example 3.

[0092] A polyurethane resin composition for display screen encapsulation in this embodiment includes the following weight

[0093] 22.5 parts of polyester resin, 12.5 parts of polyurethane resin, 47.5 parts of butanone, 8 parts of silane coupling agent KH560, 10 parts of lamellar bentonite modified whisker agent, 7.5 parts of glass fiber regulator and 3.5 parts of nano lanthanum oxide agent.

[0094] The preparation method of the flaky bentonite modified whisker agent of this embodiment is:

[0095] S01: The bentonite was heat treated at 310°C for 7.5 min, then cooled to 150°C at a rate of 3.5°C / min, and then cooled to 55°C at a rate of 2°C / min;

[0096] S02: The product of S01 is transferred to a yttrium nitrate solution for immersion treatment, the immersion pressure is 7.5 MPa, the immersion time is 15 min, and after the immersion is completed, it is filtered and dried to obtain an immersed flaky bentonite agent;

[0097] S03: adding 5.5 parts of silicon carbide whiskers, 2 parts of sodium lignin sulfonate, and 0.40 parts of a phosphate buffer solution with a pH value of 5.5 to 12.5 parts of a 5% chitosan solution, and stirring to obtain a silicon carbide whisker solution;

[0098] S04: The immersed lamellar bentonite agent and silicon carbide whisker liquid are mixed and ball-milled in a weight ratio of 5:2. The ball-milling speed is 1250 r / min and the ball-milling time is 25 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a lamellar bentonite modified whisker agent.

[0099] The mass fraction of the yttrium nitrate solution in this embodiment is 6%.

[0100] The preparation method of the glass fiber conditioning agent of this embodiment is:

[0101] S11: mixing glass fiber and sodium citrate solution in a weight ratio of 1:3 and feeding the mixture into a mixer;

[0102] S12: then add 3.5% of diethanolamine, 2% of sodium dodecylbenzene sulfonate and 3% of glycolic acid, and stir at a speed of 350 r / min for 15 min until the stirring is finished;

[0103] S13: Finally, add 5.5% of the total amount of glass fiber nano-silica sol, stir at a speed of 800 r / min for 35 minutes, wash with water, and dry to obtain a glass fiber regulator.

[0104] The mass fraction of the sodium citrate solution in this embodiment is 12.5%.

[0105] The preparation method of the nano lanthanum oxide agent of this embodiment is:

[0106] The nano-lanthanum oxide is first irradiated in a proton irradiation box for 15 minutes. After the irradiation is completed, the temperature is raised to 215°C at a rate of 2°C / min, heat-treated for 10-20 minutes, then placed in a 7.5°C sodium silicate solution with stirring and cooled to room temperature, finally washed with water and dried to obtain the nano-lanthanum oxide agent.

[0107] The mass fraction of the sodium silicate solution in this embodiment is 16%.

[0108] The irradiation power of this embodiment is 400W.

[0109] A method for preparing a polyurethane resin composition for display screen encapsulation in this embodiment comprises the following steps:

[0110] The lamellar bentonite modified whisker agent, glass fiber regulator, nano lanthanum oxide agent and silane coupling agent KH560 are sequentially added to butanone and stirred to mix well, and then polyester resin and polyurethane resin are added, stirred thoroughly at 62.5° C., and finally cooled and filtered to obtain a polyurethane resin composition for display screen encapsulation.

[0111] Comparative Example 1.

[0112] The difference from Example 3 is that no lamellar bentonite modified whisker agent is added.

[0113] Comparative Example 2.

[0114] The difference from Example 3 is that the S02 step is not used in the lamellar bentonite modified whisker agent.

[0115] Comparative Example 3.

[0116] The difference from Example 3 is that the lamellar bentonite modified whisker agent is not treated with silicon carbide whisker liquid.

[0117] Comparative Example 4.

[0118] The difference from Example 3 is that no silicon carbide whiskers are added in the preparation of the silicon carbide whisker liquid.

[0119] Comparative Example 5.

[0120] The difference from Example 3 is that no glass fiber conditioning agent is added.

[0121] Comparative Example 6.

[0122] The difference from Example 3 is that the S12 step is not used in the glass fiber conditioning agent.

[0123] Comparative Example 7.

[0124] The difference from Example 3 is that the glass fiber conditioning agent is not treated in step S13.

[0125] Comparative Example 8.

[0126] The difference from Example 3 is that no nano lanthanum oxide agent is added.

[0127] The performance tests of the products of Examples 1-3 and Comparative Examples 1-8 are as follows:

[0128]

[0129] It can be seen from Examples 1-3 and Comparative Examples 1-8 that the bonding strength, water vapor transmittance and resistance to cold and hot shock cycles of Example 3 of the present invention can be coordinated and improved. It can be seen from Comparative Examples 1-8 that the performance of the products without adding any of the flaky bentonite modified whisker agent, the glass fiber regulator and the nano lanthanum oxide agent all have a significant deterioration trend. Only by using the three in coordination and synergy, the performance effect of the product is most significant. The flaky bentonite modified whisker agent does not use the S02 step for treatment, the flaky bentonite modified whisker agent does not use the silicon carbide whisker liquid for treatment, the silicon carbide whisker is not added in the preparation of the silicon carbide whisker liquid, the glass fiber regulator does not use the S12 step for treatment, and the glass fiber regulator does not use the S13 step for treatment. The performance of the products all have a deterioration trend. Only by using the flaky bentonite modified whisker agent and the glass fiber regulator obtained by the method of the present invention, the performance effect of the product is most significant.

[0130] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0131] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A polyurethane resin composition for display screen encapsulation, characterized in that: The invention comprises the following raw materials in parts by weight: 20-25 parts of polyester resin, 10-15 parts of polyurethane resin, 45-50 parts of butanone, 6-10 parts of silane coupling agent KH560, 8-12 parts of lamellar bentonite modified whisker agent, 5-10 parts of glass fiber regulator and 2-5 parts of nano lanthanum oxide agent; The preparation method of the flaky bentonite modified whisker agent is as follows: S01: Send bentonite to 300-320℃ for heat treatment for 5-10min, then cool to 145-155℃ at a rate of 2-5℃ / min, and then cool to 55℃ at a rate of 1-3℃ / min; S02: The product of S01 is transferred to a yttrium nitrate solution for immersion treatment, the immersion pressure is 5-10MPa, the immersion time is 10-20min, and after the immersion is completed, it is filtered and dried to obtain an immersed flaky bentonite agent; S03: adding 4-7 parts of silicon carbide whiskers, 1-3 parts of sodium lignin sulfonate, and 0.35-0.45 parts of a phosphate buffer solution with a pH value of 5.5 to 10-15 parts of a 5% chitosan solution, and stirring to obtain a silicon carbide whisker solution; S04: mixing the immersed flaky bentonite agent and the silicon carbide whisker liquid in a weight ratio of 5:2 and subjecting them to ball milling treatment, with a ball milling speed of 1000-1500 r / min and a ball milling time of 20-30 min. After the ball milling is completed, washing with water and drying are performed to obtain a flaky bentonite modified whisker agent; The preparation method of the glass fiber conditioning agent is: S11: mixing glass fiber and sodium citrate solution in a weight ratio of 1:3 and feeding the mixture into a mixer; S12: then add 2-5% of diethanolamine, 1-3% of sodium dodecylbenzene sulfonate and 1-5% of glycolic acid to the total amount of glass fiber, stir at a speed of 300-400 r / min for 10-20 min, and then finish stirring; S13: Finally, add 4-7% of the total amount of glass fiber nano-silica sol, stir at a speed of 700-900r / min for 30-40min, wash with water and dry to obtain a glass fiber conditioning agent; The preparation method of the nano lanthanum oxide agent is: The nano-lanthanum oxide is first irradiated in a proton irradiation box for 10-20 minutes. After the irradiation is completed, the temperature is raised to 210-220°C at a rate of 1-3°C / min, heat-treated for 10-20 minutes, then placed in a 5-10°C sodium silicate solution with stirring and cooled to room temperature, and finally washed with water and dried to obtain the nano-lanthanum oxide agent.

2. The polyurethane resin composition for display screen encapsulation according to claim 1, characterized in that: The polyurethane resin composition for display screen encapsulation is composed of the following raw materials in parts by weight: 22.5 parts of polyester resin, 12.5 parts of polyurethane resin, 47.5 parts of butanone, 8 parts of silane coupling agent KH560, 10 parts of lamellar bentonite modified whisker agent, 7.5 parts of glass fiber regulator and 3.5 parts of nano lanthanum oxide agent.

3. The polyurethane resin composition for display screen encapsulation according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 4-8%.

4. The polyurethane resin composition for display screen encapsulation according to claim 1, characterized in that: The mass fraction of the sodium citrate solution is 10-15%.

5. The polyurethane resin composition for display screen encapsulation according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 14-18%.

6. The polyurethane resin composition for display screen encapsulation according to claim 1, characterized in that: The irradiation power is 350-450W.

7. A method for preparing a polyurethane resin composition for display screen encapsulation according to any one of claims 1 to 6, characterized in that: The following steps are involved: The lamellar bentonite modified whisker agent, glass fiber regulator, nano lanthanum oxide agent and silane coupling agent KH560 are sequentially added to butanone and stirred to mix well, and then polyester resin and polyurethane resin are added, stirred thoroughly at 60-65° C., and finally cooled and filtered to obtain a polyurethane resin composition for display screen encapsulation.

Citation Information

Patent Citations

  • Solvent-free polyurethane three-dimensional grain pattern modeling runway surface layer and preparation method thereof

    CN114854301A

  • Polyurethane composition and method for specific polyurethane articles with improved strength properties

    CN115093538A

Cited By

  • TPU (thermoplastic polyurethane) air closing film, preparation method of TPU air closing film and application of TPU air closing film in inflatable floating bridge

    CN121450086A

  • TPU air-tight membrane, its preparation method and application in inflatable floating bridge

    CN121450086B